The effectiveness of intimacy training with Islamic approach on cognitive flexibility and meaning of couples’ lives in the marriage stage referred to Bushehr counseling centers - Mohannaee, Setareh; Pourgholami, Farzad; Shahbazi, Fatemeh; Moji, Mahbobeh; Farashbandi, Reza (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The purpose of this study was the effectiveness of intimacy training with an Islamic approach on cognitive flexibility and the meaning of couples’ lives at the stage of marriage referred to counseling centers in Bushehr in 2020. Methods: The method of the present study was quasi-experimental with pre-test and post-test design with control group and the statistical population of the present study was 1225 couples in the contracting stage referring to Bushehr counseling centers. Entry and exit criteria were randomly assigned between the experimental and control groups. The experimental group received training for 8 sessions of 90 minutes (one session per week) after performing the pre-test; but the control group did not receive any training after the pre-test. The instruments of the present study were the meaning of life questionnaires of Steger et al. (2006) and the cognitive flexibility of Dennis and Vanderwall (2010). Data were analyzed using analysis of covariance and SPSS 24 software. Results: The results showed that intimacy training with an Islamic approach increased each of the components of the meaning of life, ie the existence of meaning in life and the search for meaning in the subjects in the experimental group compared to the control group. Also, intimacy training with Islamic approach increased each of the components of cognitive flexibility, ie perception, perception of controllability and perception of behavior justification in the subjects of the experimental group compared to the control group. Conclusion: The general results of this study indicate the effectiveness of intimacy training with Islamic approach on couples in the marriage stage, which ultimately leads to increased cognitive flexibility and meaning of the couple’s life. By attending meetings, they can increase intimacy by planning objective and behavioral goals.